2019
DOI: 10.1111/vop.12653
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopically guided neocanalization for treatment of nasolacrimal atresia in two horses

Abstract: Case description A yearling Thoroughbred stallion and an 8‐year‐old Saddlebred mare were evaluated for persistent mucoid ocular discharge. Clinical findings Examination of both horses revealed copious yellow‐tan mucoid ocular discharge with a negative Jones I test, absent nasal punctum, and unsuccessful anterograde nasolacrimal duct (NLD) irrigation. Clinical abnormalities were present on the right side only in one horse and bilaterally in the other. Computed tomography (CT) with contrast confirmed nasolacrima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The stent remains in place for 4–6 weeks 1 . However, as previous studies have demonstrated, horses often rub due to irritation from the stenting material, leading to early dislodgement and potential failure of the procedure 7,9 . Canaliculosinostomy has successfully redirected tear flow into the frontal and maxillofacial sinuses 2,7 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The stent remains in place for 4–6 weeks 1 . However, as previous studies have demonstrated, horses often rub due to irritation from the stenting material, leading to early dislodgement and potential failure of the procedure 7,9 . Canaliculosinostomy has successfully redirected tear flow into the frontal and maxillofacial sinuses 2,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Materials that have been reported to stent the equine NLD include red rubber catheters, 1,5 rigid open‐end ureteral stents, 9 and silastic or plastic canine urinary catheters 1,2 . These materials are often irritating, leading to early extrusion by the patient or owner intolerance 7,9 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nasolacrimal drainage system consists of the superior and inferior puncta, superior and inferior canaliculi, lacrimal sac, NL duct, and nasal puncta 1 . Various congenital and acquired diseases of the nasolacrimal duct system have been described in dogs, 2,3 rabbits, 4 cats, 5 horses, 6,7 and cattle 8 . The most common consequence of disorders of the NL duct is obstruction which results in epiphora and secondary facial dermatitis and tear staining.…”
Section: Introductionmentioning
confidence: 99%